Global Flows, Local Appropriations Facets of Secularisation and Re-Islamization Among Contemporary Cape Muslims - Bangstad, Sindre (ISIM Dissertations, 2007)
Global Flows, Local Appropriations; Facets of Secularisation and Re-Islamization Among Contemporary Cape Muslims is the first ethnographic study of muslims in Cape Town, South Africa at this level in 25 years. It explores processes of secularisation and re-islamization among Cape Muslims in the context of a post-apartheid South Africa in which liberal and secular values have attained considerable purchase in the new political and social elites. Fractured by status, ethnicity and religious orientation, Cape muslims have responded to these changes through an ambiguous accomodation with the new order. This study explores this development through chapters on conversions to Islam among black Africans in Cape Town, Cape women's experiences with polygyny, Cape muslims and HIV/AIDS, the status of Islam in a prison Cape Town in the post-apartheid era and on contestation over rituals among Cape muslims.